Modality Analysis on the Official Website of Indonesian Tourism - Rahmasari, Shafira; Lauwren, Stefanny (Universitas Negeri Semarang, 2020)
Tourism is believed as the primary motivation to improve the economy of a country. In order to attract some tourists to visit tourism destinations in Indonesia, The Ministry of Tourism establishes an official website to share the information regarding the tourism destinations, activities, and attractions. This study is conducted to observe how the official website of Indonesian tourism utilizes modality to present Indonesian tourism discourse. This paper analysed ten destination highlights of the website covering the areas of Medan, Raja Ampat, Bali, Banyuwangi, Bintan Island, Jakarta, Yogyakarta, Bandung, Makassar, and Lombok through Discourse Analysis approach utilizing Halliday’s Systemic Functional Linguistics. This paper found modality is used in the forms of probability, usuality, inclination, and obligation. Those different types of modality are employed to describe three domains of tourism discourse: itineraries and access, place to play, and authenticity. It is concluded that the government uses the website to ensure the readers’ being well informed of Indonesian tourism destinations and safety during their visit to Indonesia.